Overcoming clinical inertia in insulin initiation in primary care for patients with type 2 diabetes: 24-month follow-up of the Stepping Up cluster randomised controlled trial. Issue 5 (October 2017) - Manski-Nankervis, Jo-Anne; Furler, John; O'Neal, David; Ginnivan, Louise; Thuraisingam, Sharmala; Blackberry, Irene
Highlights: Stepping Up consists of GP and practice nurse insulin initiation with diabetes educator support. Stepping Up is associated with improved HbA1c, maintained at 24 months. Ongoing diabetes educator mentoring and support may facilitate treatment intensification. Abstract: Aim: To examine the two-year impact of Stepping Up, a general practice based model of care intervention for insulin initiation and titration in Australia. Methods: 266 participants from 74 general practices participated in the Stepping Up cluster randomised controlled trial between 2012–2014. Control practices received training in the model of care on completion of the 12-month trial. Patients were followed for 24 months. Participant baseline characteristics, insulin and non-insulin medication use were summarised for each study group. Linear mixed-effects models with random intercepts were used to estimate differences in mean outcome (HbA1c and weight) between the study groups using restricted maximum likelihood estimation. Results: At baseline 61% of patients were male, mean (SD) age 62 (10) years, diabetes duration 9 (5, 13) years and mean (95% CI) HbA1c was 8.9 (8.8–9.1)% (74 (73–76) mmol/mol) for both groups. There was a significant between group difference at 6 months which was sustained at 24 months; Mean (95% CI) HbA1c at 24 months in the intervention group was 7.6 (7.5–7.8)% (60 (58–62) mmol/mol) and 8.0 (7.7–8.4)% (64 (61–68) mmol/mol) in the control group. At 24 months 97 (71.3%) of the intervention group and 26 (31.0%) of the control group were prescribed insulin; there was no significant difference in weight. Use of non-insulin anti-hyperglycaemic agents was similar in both groups with the exception of dipeptidyl peptidase-4 inhibitors which were prescribed more frequently in the control group (30(36%) vs 21(16%)). Conclusion: Stepping Up was associated with improved glycaemic control compared to usual care for 24 months, suggesting that the model facilitated more timely treatment intensification. Ongoing RN-CDE support may be needed to facilitate ongoing treatment intensification.